Characterization of Physical Properties and Sensory Evaluation of Pletok Bir Enriched with Apple Juice - Luh Dian Rna Fajarini; I Gede Arie Mahendra Putra; Putu Julyantika Nica Dewi; I Wayan Ryantama Swastika Braja; Riel Jeremy Jordan Umboh (Warmadewa University Press, 2025)
This study aimed to determine the optimal concentration of apple juice as a flavor enhancer in pletok bir, a traditional Betawi drink, through evaluation of three ratio treatments (0:1/control, 1:1, and 3:1 v/v). Analysis of physical properties (pH, viscosity) and sensory attributes (color, aroma, taste, acceptability) using a 5-point hedonic scale showed that increasing apple juice concentration decreased pH from 7.33 to 4.31 and increased viscosity (0.107-0.125 mPa-s). A 3:1 ratio achieved the highest taste preference (score of 3.76) with an optimal viscosity balance (0.125 mPa-s), reducing bitterness and providing subtle sweetness without obscuring the characteristic spicy aroma. In contrast, the 1:1 ratio resulted in lower acceptability (score 3.08) due to flavor imbalance. Overall acceptability scores ranged from 3.2-3.64 (neutral-moderately like), reflecting moderate consumer preference. These findings indicate that the addition of apple juice at a 3:1 ratio can enhance the sensory appeal of pletok bir while maintaining its traditional essence, offering an innovation to expand the market through flavor diversification.